Quartz C-axis fabric along Main Central Thrust (MCT), Garhwal Himalaya, India - Singh, V. K. (Journal of Nepal Geological Society, 1995)
The granite-gneisses are thrust over the less metamorphosed quartzites along the Main Central Thrust (MCT) in Garhwal Himalaya. The quartz C-axes fabrics from the plastically deformed quartzites and granite-gneisses were studied with the help of universal stage in XZ sections. The measurements of quartz C-axes in quartzite exhibit single and cross girdles. The C-axes maxima are located at the peripheries and towards the Y-axis. The quartz C-axes maxima in granite-gneisses are characterised by diffuse cross girdles with unequally populated pattern. The concentration of the quartz C-axes maxima is recorded progressively towards Y-axis.The single inclined girdles are generally exhibited by the quartz grains due to simple shear. The cross girdle patterns are due to conjugate direction of shear acting simultaneously under the influence of non-coaxial flattening (Bouchez and Pecher, 1981). The fabric of C-axes, commonly encountered in the shear zone are characterised by the maxima forming cross girdles which are asymmetric to the MCT transport direction. The quartz C-axes fabrics in quartzite formed by glide on the basal and rhomb systems. The deformation movements were of sinistral type during the formation of the MCT.